(untitled) (Revista Inclusiones, 2018)
The Russian Federation is now in a state of escalating competition as a result of joining the World Trade Organization (WTO), the formation of a single Euro-Asian economic and customs area, economic sanctions by a number of Western countries and a retaliatory food embargo from Russia, etc. Therefore, the search for new adaptive mechanisms and instruments for institutional support of sustainable agro-industrial activity becomes an inevitable and primary objective for state authorities, the scientific community and business. The paper analyzes the national interests of the Russian Federation in the food sector. Based on a scientific analysis, the author concludes that ensuring food security is associated with overcoming the influence of negative factors that form these threats for the Russian food market leading to a decrease in the number of main types of food products, the absence or deterioration of their nutritional and energy value. According to the author, it is necessary to develop and clarify theoretical, methodological and practical provisions for the development of agro-industrial territorial systems that meet the objectives of ensuring national food security and import substitution of the main types of agricultural products and food. This causes the task of achieving constructive intra-industry and inter-industry cooperation, as well as the formation of an appropriate institutional environment as key factors affecting the sustainability of the agrarian part of the economy. Therefore, we need both new managerial decisions and updated criteria and parameters for the development of the agro-industrial complex at various territorial levels and in the sectoral context. To highlight the problem stated in the article, the author used a synthesized approach that incorporates certain provisions of the institutional, systemic, evolutionary, and strategic approaches to management.